КЕРУВАННЯ РЕЖИМАМИ РОЗПОДІЛЬНИХ ЕЛЕКТРОМЕРЕЖ МІСТ В УМОВАХ СЛАБКОЇ КОРЕЛЯЦІЇ ГРАФІКІВ АКТИВНОЇ ТА РЕАКТИВНОЇ ПОТУЖНОСТЕЙ - Говоров, П.П.; Новський , В.О.; Говоров, В.П.; Кіндінова, А.К. (Інститут електродинаміки НАН України, Київ, 2020)
Settlement and experimental studies of the use of filter-compensating devices for use in lighting electrical networks and phase-switched booster transformers for controlling the flows of active and reactive powers are presented. The analysis of component capacities in the conditions of non-linearity of the characteristics of their consumers and low correlation of voltage and reactive power in urban distribution networks is carried out. References 9, Figures 5.